2021
DOI: 10.1093/jpe/rtab116
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive plasticity in response to light and nutrient availability in the clonal plantDuchesnea indica

Abstract: Aims Phenotypic plasticity enables plants to buffer against environmental stresses and match their phenotypes to local conditions. However, consistent conclusive evidence for adaptive plasticity has only been obtained for a few traits. More studies on a wider variety of plant functional traits and environmental factors are still needed to further understand the adaptive significance of plasticity. Methods We grew 21 genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In detail, the results in this study showed that shade triggers morphological shade avoidance syndrome (SAS) both in NG and OG offspring, with higher plant vegetative height, leaf length, leaf width, and lower ramet number, stem diameter, and leaf inclination angle (Figure 2), which can be interpreted as active plastic responses [24,70]. To cope with spatial and temporal variations in light, plants often display a broad spectrum of phenotypic plasticity [71].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In detail, the results in this study showed that shade triggers morphological shade avoidance syndrome (SAS) both in NG and OG offspring, with higher plant vegetative height, leaf length, leaf width, and lower ramet number, stem diameter, and leaf inclination angle (Figure 2), which can be interpreted as active plastic responses [24,70]. To cope with spatial and temporal variations in light, plants often display a broad spectrum of phenotypic plasticity [71].…”
Section: Discussionmentioning
confidence: 83%
“…Earlier studies have also indicated that plants tend to produce larger leaves and longer internodes to intercept light efficiently [72,73]. Shade with a reduction in the R/FR ratio negatively affected vegetative ramet number [70]. Reallocation of energy resources from storage organs (e.g., root) to stem and leaf enabled the shaded plants to outgrow their competitors and enhance light capture [74].…”
Section: Discussionmentioning
confidence: 97%
“…Clonal plants can successfully adapt to new environments, allowing them to dominate many ecosystems [ 27 , 52 ] owing to traits such as clonal plasticity, which enables the production of different phenotypes in different environments [ 59 , 61 ], clonal integration, facilitating translocation and sharing of resources and/or signals between ramets connected by clonal organs [ 60 , 70 ]; clonal foraging, leading to the allocation of more roots, shoots, and/or whole ramets in high-resource patches [ 9 , 10 , 72 ], and trade-offs between different clonal growth forms [ 73 , 76 ]. Most clonal plants have the capacity for both sexual and clonal reproduction [ 22 , 27 , 28 , 41 ].…”
Section: Introductionmentioning
confidence: 99%